2018
DOI: 10.2147/ndt.s162896
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum inflammatory markers on the prognosis of adult and pediatric patients with Guillain–Barré syndrome

Abstract: ObjectiveThe aim of this study was to evaluate blood neutrophil–lymphocyte ratio (NLR), platelet–lymphocyte ratio (PLR), C-reactive protein (CRP), and albumin levels for their prognostic value in adult Guillain–Barré syndrome (GBS-A) and pediatric Guillain–Barré syndrome (GBS-P) patients.Patients and methodsWe retrospectively analyzed the medical records of 68 Guillain–Barré syndrome (GBS) patients (36 adults, 32 children) who were treated as inpatients at Harran University Faculty of Medicine, Neurology and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 30 publications
2
34
0
2
Order By: Relevance
“…Thirty of the 60 studies were excluded after reading the full text because they lacked the necessary data ( n = 7); lack of a control group ( n = 9); reported ex vivo cytokine data ( n = 4); single case reports ( n = 2), and blood or CSF cytokines were analyzed in less than three studies ( n = 8). Thus, a total of 30 studies comprising 1,302 patients with GBS and 1,073 healthy individuals were included in the meta-analysis (Sharief et al, 1993; Exley et al, 1994; Sindern et al, 1996; Creange et al, 1998; Hohnoki et al, 1998; Ossege et al, 2000; Press et al, 2001; Radhakrishnan et al, 2003, 2004; Deng et al, 2008; Nyati et al, 2010, 2011; Sainaghi et al, 2010; Li et al, 2012, 2013, 2014, 2018a,b; Liang et al, 2012; Wang et al, 2012; Han et al, 2014; Beppu et al, 2015; Du et al, 2015; Chang et al, 2016; Doncel-Perez et al, 2016; Zhang et al, 2016; Kharwar et al, 2017; Debnath et al, 2018a,b; Ethemoglu and Calik, 2018) (Flowchart see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty of the 60 studies were excluded after reading the full text because they lacked the necessary data ( n = 7); lack of a control group ( n = 9); reported ex vivo cytokine data ( n = 4); single case reports ( n = 2), and blood or CSF cytokines were analyzed in less than three studies ( n = 8). Thus, a total of 30 studies comprising 1,302 patients with GBS and 1,073 healthy individuals were included in the meta-analysis (Sharief et al, 1993; Exley et al, 1994; Sindern et al, 1996; Creange et al, 1998; Hohnoki et al, 1998; Ossege et al, 2000; Press et al, 2001; Radhakrishnan et al, 2003, 2004; Deng et al, 2008; Nyati et al, 2010, 2011; Sainaghi et al, 2010; Li et al, 2012, 2013, 2014, 2018a,b; Liang et al, 2012; Wang et al, 2012; Han et al, 2014; Beppu et al, 2015; Du et al, 2015; Chang et al, 2016; Doncel-Perez et al, 2016; Zhang et al, 2016; Kharwar et al, 2017; Debnath et al, 2018a,b; Ethemoglu and Calik, 2018) (Flowchart see Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…GBS, as a serious autoimmune disorder, may in these conditions induce a higher level of inflammation resulting in an increase in the serum C-reactive protein. CRP has already been used to predict the need for mechanical ventilation and prognosis in GBS patients with inconsistent results across studies ( 19 , 27 , 28 ). Altaweel et al found in 24 GBS patients a statistically significant positive correlation between clinical severity assessed by the Hughes disability scale and serum CRP level ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several studies have also proved the prognostic value of NLR for systematic inflammatory diseases in pediatric settings. 20,21 Interestingly, some of these pediatric patients need to accepted immunotherapy targeting on CTLA-4 and programmed death (PD)-1 receptors, which is similar to post-transplant immunotherapy. 22,23 Thus, we can assume that LT patients may share similar immune-inflammatory backgrounds with some cancer patients, and NLR could be a reliable and accessible indicator to reflect it.…”
Section: Discussionmentioning
confidence: 99%
“…Our study advances this discussion by focusing on infants with congenital BA. Recently, several studies have also proved the prognostic value of NLR for systematic inflammatory diseases in pediatric settings 20,21 . Interestingly, some of these pediatric patients need to accepted immunotherapy targeting on CTLA‐4 and programmed death (PD)‐1 receptors, which is similar to post‐transplant immunotherapy 22,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation